Students’ Problem-Solving Ability through Problem-Based Learning and Ricosre Learning Model in Modern Biotechnology - Fatmawati, Umi; Utomo, Tegar Budi; Nurmiyati (BIOEDUKASI: Jurnal Biologi dan Pembelajarannya, 2025)
Problem-solving abilities is important to master so that students can analyze problems, evaluate scientific information, and make decisions based on data. Problem-solving ability can be empowered through interactive learning models. This study aims to determine students' problem-solving ability differences with the Problem-Based Learning model and the Ricosre model on modern biotechnology material. This study used a quasi-experimental research method with a pretest-posttest control group design conducted at SMAN 3 Sukoharjo. The instruments used in this study were problem-solving ability test questions, observation sheets, and student interviews. The results showed a difference in problem-solving ability in classes with PBL and Ricosre models based on the Ancova test results of 0.00. Furthermore, the N-Gain test found that the Ricosre model resulted in an increase in students' problem-solving ability of 0.556 which is classified as moderate is higher when compared to the Problem-Based Learning model, which resulted in an N-Gain test value of 0.361 which is classified as moderate. These findings confirm that the Ricosre learning model is effective in improving students' problem-solving abilities and can be applied to other science subjects in secondary schools and universities because this model involves discovering alternative strategies based on prior experiences gained through intensive discussion and repeated problem-solving, there by familiarising students with problem-solving that promotes the mastery of 21st-century skills